2010
DOI: 10.1007/s12393-010-9030-4
|View full text |Cite
|
Sign up to set email alerts
|

An Update on High Hydrostatic Pressure, from the Laboratory to Industrial Applications

Abstract: High hydrostatic pressure has become an industrial reality, and although there are still many aspects under research, today it is possible to buy high-pressurized products in many countries. Indeed, pasteurization of food products using elevated pressure at room temperature has been accepted by regulatory agencies for commercial use. The quality displayed in such products includes better nutritional retention, fresh-like flavor, improved color, texture, and taste, and extended shelf life compared to thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(74 citation statements)
references
References 90 publications
0
74
0
Order By: Relevance
“…High hydrostatic pressure (HHP), which is considered as one of the most important innovations in food processing in 50 years (Balasubramaniam, Farkas, & Turek, 2008), has become a reality in the food industry and has spread worldwide due to its advantages of Innovative Food Science and Emerging Technologies xxx (2014) preserving the quality and organoleptic properties of foods (Bermúdez-Aguirre & Barbosa-Cánovas, 2011;Donsì, Ferrari, & Maresca, 2010). By mid-2008, about 125 pieces of industrial HHP equipment were in production for food processing worldwide and almost 85% of these pieces equipment were installed after 2000 (Tonello, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High hydrostatic pressure (HHP), which is considered as one of the most important innovations in food processing in 50 years (Balasubramaniam, Farkas, & Turek, 2008), has become a reality in the food industry and has spread worldwide due to its advantages of Innovative Food Science and Emerging Technologies xxx (2014) preserving the quality and organoleptic properties of foods (Bermúdez-Aguirre & Barbosa-Cánovas, 2011;Donsì, Ferrari, & Maresca, 2010). By mid-2008, about 125 pieces of industrial HHP equipment were in production for food processing worldwide and almost 85% of these pieces equipment were installed after 2000 (Tonello, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reviews have been written concerning effects of HHP on microorganisms (Bermúdez-Aguirre & Barbosa-Cánovas, 2011;Considine, Kelly, Fitzgerald, Hill, & Sleator, 2008;Farkas & Hoover, 2000;Matser, Krebbers, van den Berg, & Bartels, 2004;Patterson, 2005;Zhang & Mittal, 2008). However, to the best of the author's knowledge there is no review on multi-pulsed HHP inactivation of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…High hydrostatic pressure (HHP) processing is a non-thermal, energy-efficient and emergent inactivation technology, which has been widely studied to eliminate pathogenic microorganisms in foods (Bermúdez-Aguirre and Barbosa-Cánovas, 2011). HHP-treated foods maintain most of their natural characteristics like colour, flavour and health promoting substances (Kingsley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure processing (HPP) technology has been developed as an alternative to thermal processes with the aim of obtaining microbiologically safe food products while avoiding undesirable changes in the sensory, physicochemical, and nutritional properties of foods (Bermu´dez-Aguirre & Barbosa-Ca´novas, 2011;Campus, 2010;Mu´jica-Paz, Valdez-Fragoso, Tonello Samson, Welti-Chanes, & Torres, 2011;Palou, Lo´pez-one of the innovative food processing technologies most accepted by consumers (Cardello, 2003;Cardello, Schutz, & Lesher, 2007;Evans & Cox, 2006). A recent development, not yet commercialized but with an application already approved by the US Food & Drug Administration (www.nafwa.org/blog/, accessed 5 March 2009), is the use of pressure treatments at higher temperatures, a method known as pressure assisted thermal processing (PATP) (Bermu´dez-Aguirre & Barbosa-Ca´novas, 2011;Mu´jica-Paz et al, 2011;Torres, Sanz, Otero, Pe´rez Lamela, & Saldan˜a, 2009b;.…”
Section: Introductionmentioning
confidence: 99%
“…A recent development, not yet commercialized but with an application already approved by the US Food & Drug Administration (www.nafwa.org/blog/, accessed 5 March 2009), is the use of pressure treatments at higher temperatures, a method known as pressure assisted thermal processing (PATP) (Bermu´dez-Aguirre & Barbosa-Ca´novas, 2011;Mu´jica-Paz et al, 2011;Torres, Sanz, Otero, Pe´rez Lamela, & Saldan˜a, 2009b;. Regarding HPP effects on food composition, research has shown a higher retention of nutrients and functional compounds including no changes in antioxidant capacity when compared with other preservation processes such as thermal treatments (Oey, Lille, van Loey, & Hendrickx, 2008;Oey, van der Plancken, van Loey, & Hendrickx, 2008); however, there are still very few studies reporting PATP effects on foods (Ramirez, Saraiva, Pe´rez Lamela, & Torres, 2009).…”
Section: Introductionmentioning
confidence: 99%